Suitability of aquatic plant fibers for handmade papermaking - Bidin, Nordiah; Zakaria, Muta Harah; Bujang, Japar Sidik; Abdul Aziz, Nur Aznadia (Hindawi Limited, 2015)
Increasing concerns for future fiber supplies in pulp and paper industries has shifted interest in nonwood sources from agriculture residues and aquatic plants. Aquatic plants with short growth cycles, in abundance, and with low lignin are a potential fiber source. Five aquatic plant species, Cyperus digitatus, Cyperus halpan, Cyperus rotundus, Scirpus grossus, and Typha angustifolia, were examined for fiber dimensions and chemical composition (cellulose, lignin) and compared with other nonwood plants. All aquatic plants possessed short (length, 0.71–0.83 mm) and thin (diameter, 9.13–12.11 µm) fibers, narrow lumen (diameter, 4.32–7.30 µm), and thin cell wall (thickness, 2.25–2.83 µm) compared with most other nonwood plants. Slenderness ratio ranged from 73.77 to 89.34 with Typha angustifolia having the highest ratio. Except for Scirpus grossus, the flexibility coefficient ranged from 52.91 to 58.08. Scirpus grossus has low Runkel ratio, 0.84 ± 0.17. Fiber characteristics, short and thin fibers, Slenderness ratio >60, flexibility coefficient within 50–75, and Runkel ratio <1, are suitable for papermaking. Cellulose content of Cyperus rotundus (42.58 ± 1.32%), Scirpus grossus (36.21 ± 2.81%), and Typha angustifolia (44.05 ± 0.49%) >34% is suitable for pulp and papermaking. Lignin content in aquatic plants in the present study ranged 9.54–20.04% and below the wood lignin content of <23–30% encountered in pulp and papermaking. Handmade paper sheets produced for paperboard, craft, and decorative purposes are with permissible tensile strength, breaking length, and low moisture content.